Effect of panchagavya and recommended dose of fertilizers on growth, nutrient content and productivity of transplanted rice (Oryza sativa) under middle Gangetic plain of India - UPADHYAY, P K; SEN, AVIJIT; PRASAD, S K; SINGH, YASHWANT; SRIVASTAVA, J P; SINGH, S P; SINGH, R K (The Indian Journal of Agricultural Sciences, 2018)
A field trial was conducted at the Agricultural Research Farm, Banaras Hindu University during 2013-14 and 2014-15 to study the effect of time and rate of panchagavya application and recommended dose of fertilizers (RDF) on growth, nutrient content and productivity of transplanted rice (Oryza sativa L.). Interaction of panchagavya and RDF exhibited significant effect on dry matter accumulation, productive tillers/m2 as well as grain and straw yields of rice. Enhancement by 42% in the number of productive tillers/m2 and 33% in grain yield was observed with the combination of D4 (seedling root dip + one spray at 30 DAT @ 6% + application through irrigation water at 60 DAT) + 100% RDF over 60%RDF without panchagavya. Application of panchagavya (D4) significantly increased nitrogen, phosphorus and potassium content in grain and straw following higher total uptake of these elements.120% RDF significantly increased the N, P and K content in grain and straw over 60, 80 and 100% RDF. Productive tillers/m2 , panicle length and filled spikelets/panicle showed linear response with yield. Residual effect of panchagavya (D4) in combination with 100% RDF recorded 27% increment in the yield of lentil.